A public practical theological theory for religious education of secularised youth - Dreyer, Yolanda (HTS teologiese studies, 2004)
In the postmodern world young people no longer accept the values advocated by the institutionalised church as unquestionably relevant to their lives, one of the reasons for this being that the supremacy of the Christian faith has given way to a secularised society. Public practical theology includes the public as one of its audiences. In this paper the point of departure is a reflection-theory and not the praxis as such. This theory focuses on everyday concerns and issues in order to facilitate a dialogue between theology and the social sciences. The article aims to reflect on the enhancement of the experience of transcendence in the everydayness of the present-day youth. It argues that the agency theories of Anthony Giddens and Pierre Bourdieu can provide a theoretical basis and method for public religious education.